Studi kasus pola asuh orang tua terhadap perkembangan anak: Dampak kesibukan orang tua dalam pola asuh perkembangan anak dalam jangka panjang - Fitriyah, Ana Nur; Aristawati, Galuh; Maghfiroh, Firda Miftahul (Maliki Interdisciplinary Journal, 2024)
The lack of parenting provided by parents to their children's development due to their busy schedules has the potential to affect the quality of parent-child relationships in the future. As a result, the limited interactions that make up parenting can have a negative impact on children's emotional, social and cognitive development. The negative impacts include decreased academic performance, behavioral problems, and a tendency to be ignorant of their surroundings. This research aims to find out the mistakes of parents' parenting of children who lack supervision and affection to cause long-term effects. The method used in the research is a literature study. The results of the research on parenting mistakes due to busyness and lack of affection from childhood cause distance and distrust in the long run. It is important to set priorities in parenting that are responsive and supportive of children's development, and support from the family and community, or wider can also play an important role in their development. The conclusion of the study is that parenting mistakes due to busy work have serious consequences for children's development. Therefore, concerted efforts from families, communities, and other relevant parties need to be made to ensure that children receive adequate attention and care to optimally realize their potential in various aspects of life.